Polyphasic Approach Utilized for the Identification of Two New Toxigenic Members of Penicillium Section Exilicaulis, P. krskae and P. silybi spp. nov - Labuda, Roman; Bacher, Markus; Rosenau, Thomas; Gasparotto, Erika; Gratzl, Hannes; Doppler, Maria; Sulyok, Michael; Kubátová, Alena; Berger, Harald; Cank, Kristof; Raja, Huzefa A; Oberlies, Nicholas H; et al. (Journal of fungi (Basel, Switzerland), 2021)
Two new species, Penicillium krskae (isolated from the air as a lab contaminant in Tulln (Austria, EU)) and Penicillium silybi (isolated as an endophyte from asymptomatic milk thistle (Silybum marianum) stems from Josephine County (Oregon, USA)) are described. The new taxa are well supported by phenotypic (especially conidial ornamentation under SEM, production of red exudate and red pigments), physiological (growth at 37 °C, response to cycloheximide and CREA), chemotaxonomic (production of specific extrolites), and multilocus phylogenetic analysis using RNA-polymerase II second largest subunit (RPB2), partial tubulin (benA), and calmodulin (CaM). Both new taxa are resolved within the section Exilicaulis in series Restricta and show phylogenetic affiliation to P. restrictum sensu stricto. They produce a large spectrum of toxic anthraquinoid pigments, namely, monomeric anthraquinones related to emodic and chloremodic acids and other interesting bioactive extrolites (i.e., endocrocin, paxilline, pestalotin, and 7-hydroxypestalotin). Of note, two bianthraquinones (i.e., skyrin and oxyskyrin) were detected in a culture extract of P. silybi. Two new chloroemodic acid derivatives (2-chloro-isorhodoptilometrin and 2-chloro-desmethyldermoquinone) isolated from the exudate of P. krskae ex-type culture were analyzed by nuclear magnetic resonance (NMR) and liquid chromatography-mass spectrometry (LC-MS).
Keywords: red exudate; secondary metabolites; Penicillium restrictum group; milk thistle; cycloheximide tolerance; mycotoxins